2018
DOI: 10.4236/me.2018.910106
|View full text |Cite
|
Sign up to set email alerts
|

Public Debt and Economic Growth: A Scissor Effect in Developing Countries? The Case of Gabon

Abstract: The multiple attempts at empirical evidence, yet recent, fail to truly dispel the theoretical vagueness of the effects of public debt on economic growth. The aim of this work is to demonstrate that public overindebtedness negatively impacts economic activity in developing countries. From estimation by the generalized moments' method in the system of the relationship between economic growth and outstanding public debt on data of the Gabonese economy, we get that an increase in the public debt in this country, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The study provided some insight on how the potential benefits of debt have been curtailed in most African countries due to misappropriation of resources. Bidzo (2018) further demonstrated that external over-borrowing impacted negatively on economic growth in the Gabonese economy. The study used GMM model to produce results that revealed considerable deterioration in economic growth due to increase in external debt.…”
Section: External Debt and The Economymentioning
confidence: 96%
“…The study provided some insight on how the potential benefits of debt have been curtailed in most African countries due to misappropriation of resources. Bidzo (2018) further demonstrated that external over-borrowing impacted negatively on economic growth in the Gabonese economy. The study used GMM model to produce results that revealed considerable deterioration in economic growth due to increase in external debt.…”
Section: External Debt and The Economymentioning
confidence: 96%
“…The study provided some insight into how the benefits of sovereign debt have been short-lived in most African countries, due to the misappropriation of resources. Bidzo (2018) further demonstrated that public over-borrowing impacted negatively on economic growth in the Gabonese economy. The GMM model was employed to produce the result, which showed that an increase in public debt led to considerable deterioration in economic activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The direct favourable effect of domestic public debt, and the direct adverse effect of foreign public debt, align partially with the findings of some studies that reported only the positive or negative impact of sovereign debt. These studies include Ssempala et al (2020), Bidzo (2018) and Asteriou et al (2021). However, SSA countries may need to reverse the negative impact of foreign public debt on economic growth, by ensuring that the external debt burden does not exceed the IMF/World Bank prescribed optimum level of 30% (IMF, 2018).…”
Section: The Implications Of Studymentioning
confidence: 99%
“…3) Gabon also records a high level of public debt denominated in foreign currency for more than a decade (Bidzo, 2018). Under these conditions, fiscal devaluation would be an interesting economic policy tool, since it is a budget-neutral measure and therefore prevents the increase of the public debt.…”
Section: Introductionmentioning
confidence: 99%